PERBEDAAN JENIS SENYUM ANTARA LAKI-LAKI DAN PEREMPUAN BERDASARKAN BENTUK LENGKUNG SENYUM PADA SISWA SMK NEGERI 6 PADANG - Redha Fauzana; Emriadi Emriadi; Eni Rahmi (Faculty of Dentistry Universitas Andalas, 2018)
Smile is one of the facial expression that are essential in expressing friendliness, agreement, and appreciation. Most patients that come to dentist to have treatment for an attractive smile. One of the component to make an attractive smile is smile arch. Smile arch have been the interest of the orthodontist in recent years. Smile arch is the relationship between a hypothetical curve drawn along the edges of the maxillary anterior teeth and the inner contour of the lower lip in smile. This study was to differ male and female’s smile type base on smile arch. This study was to evaluate of smile type based on smile arch with gender. A total of 31 females and 31 males were selected among criteria inclusion. Photographs taken with digital camera showing the subjects with a posed smile were used for this study and Adobe photoshop used to determine the smile arch. Student Mann Whitney test were used for statistical analysis. The resulting data showed that significantly difference (p<0,05) between smile arch and gender. The most common female’s smile are parallel smile (64.5) and male’s smile are straight smile (51.6%). In this study concluded that the curvature of the incisal edge anterior maxilla appears to be more pronounced or parallel for woman than for a men.